Enhancing Students’ Writing Skill Through Blogging - Luthfiyah Apriani; Melati Melati (Edu-Ling: Journal of English Education and Linguistics, 2018)
Nowadays, people are expected to be able to write and literate. As one of the important skills in language learning, writing has been considered as an important role in all aspects of life. In order to help our students having a good skill in writing, the use of technology is chosen to be integrated in the learning process. And Blogging is one of the activity that can be used to motivate the students to write actively and constructively. By using blog, teachers can help students to write constructively, promote student’s autonomy and enhance their motivation.